PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA DAERAH SERTA ANALISIS FLYPAPER EFFECT KABUPATEN / KOTA DI JAWA TENGAH TAHUN 2006 – 2008 - N. Masdjojo, Gregorius; Sukartono, Sukartono (Jurnal Ilmiah Telaah Manajemen, 2009)
The purposes of this study are to test the influence of Local Government Original Receipt (LGOR) and Balancing Funds (BF) to the Regional Expenditure (RE) and to analyze the districts flypaper effect in CentralJava Province on the period of 2006 to 2008. The object of this research are the 35 districts / cities in Central Java Province which have published their reports of income and expenditure budget area (budget). Data andmodel have fullfiled the Econometrics tests. The LGOR, the GAF and the RS have positive significant effect on RE, while the SAF has not significant effect on RE.The results of t test comparisons, sig, R and R Square forthe GAF to the RE is greater than the revenue of RE, so that RE has flypaper effect. Keywords : Local Government Original Receipt (LGOR), Balancing Funds (BF), GeneralAllocation Funds (GAF), Revenue Sharing (RS), Special Alocation Funds (SAF), Regional Expenditure (RE), Flypaper Effect